Smart robot lawn mower Robot lawn mower without need for a boundary cable around the lawn - Andersson, Petter; Labe, Filip; Mejervik Derander, Jesper; Moen, Erik; Nitsche, Alex; Wennerberg, Eric (My University, 2018)
Robot lawn mowers currently available on the market mostly use a bounding cable that is installed at the edges of the lawn and around obstacles. This allows the robot to stay on the grass and not hit any obstacles. Installing this cable can be costly and time consuming, and it is difficult to change once in place. The purpose of this project is to evaluate if it is possible to develop a product that does not need the bounding cable. The result of this project is a prototype that navigates without the need of a bounding cable. Instead it uses a combination of a camera, GPS, and ultrasound sensors. The prototype can sufficiently navigate on a closed area and detecting obstacles. It can not detect non physical edges for example not visible property lines. The conclusion reached is that the techniques used in this project is useful for developing a robot lawn mower but that they all need some adjustment. Especially the GPS needs to be replaced or improved to gain the edge detection correctly.
Keywords: Data- och informationsvetenskap; Computer and Information Science